OPTIMIZATION OF THE AMOUNT OF COKE FILLING USAGE IN CATHODIC PROTECTION SYSTEMS FOR AN ANODE GROUNDING MODEL IN THE FORM OF A HEMISPHERE - V. G. Kiselev; E. N. Ruzich; C. V. Chung (Известия высших учебных заведений: Проблемы энергетики)
In this work, we calculated the optimal amount according to "annualized costs" criteria on the basis of model representations for the anodic grounding of the cathodic protection system in the form of a single hemisphere, which is located on the surface of the ground and contains coke backfilling. At the same time, calculations were made for a similar grounding, but without the use of coke filling, which allowed comparative analysis and calculation of their comparative economic efficiency, depending on the specific resistance of the soil. As a result of these calculations, we proposed a modernized anode ground with a normalized amount of coke filling, that has increased safety in comparison with the traditional product, since it allows to reduce  risks, caused by generation of positive DС stray currents of cathodic protection system, to other underground metal constructions. This quality of the proposed anode  grounding is especially important in urban areas and at the  territories of large industrial facilities characterized by an increased density of underground metal structures.